2023
DOI: 10.3389/fpsyt.2023.1222931
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between depression, healthy lifestyle behaviors and internet addiction: a cross-sectional study of the athlete university students in Turkey

Abstract: IntroductionMental health research exists for university students in the areas of prevalence and association of depression, internet addiction and healthy lifestyle behaviors. However, the studies examining prevalence rates and these relationships in athlete university students are needed. This study aimed to evaluate the relationship between depression, healthy lifestyle behaviors and internet addiction among athlete university students in Turkey.MethodsA cross-sectional design was conducted, measuring depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Additionally, in a large sample study of Chinese college students, a significant relationship between internet addiction and depression was found 39 , and internet addiction significantly predicted subsequent levels of depression in college students 40 . This relationship also exists in other countries and regions 41 44 . Based on the above review, we can establish the second hypothesis of this study, which is that internet addiction plays a mediating role in the relationship between alexithymia and depression in college students.…”
Section: Introductionmentioning
confidence: 69%
“…Additionally, in a large sample study of Chinese college students, a significant relationship between internet addiction and depression was found 39 , and internet addiction significantly predicted subsequent levels of depression in college students 40 . This relationship also exists in other countries and regions 41 44 . Based on the above review, we can establish the second hypothesis of this study, which is that internet addiction plays a mediating role in the relationship between alexithymia and depression in college students.…”
Section: Introductionmentioning
confidence: 69%
“…It’s strongly negatively correlated with self-harm even suicide, and worthlessness, marking these as the strongest negative edges within the network. Spiritual growth encompasses pursuing long-term life goals, experiencing oneself as positively developing and changing, gaining a sense of belonging, and maximizing the potential for a healthy life through goal-directed efforts ( 41 , 82 ). Importantly, signs of depression are also characteristic of a lack of spirituality, Leung found that spiritual development significantly reduced depression, anxiety, and stress in adolescents while enhancing their self-confidence ( 83 ).…”
Section: Discussionmentioning
confidence: 99%
“…Substantial studies have reported on the predictive factors associated with Internet addiction and depressive symptoms (22,(31)(32)(33). In this study, based on the results of our previous studies on the prevalence and predictors of Internet addiction and depressive Regarding individual factors, gender and positive youth development were chosen.…”
Section: Predictive Factors Associated With Internet Addiction and De...mentioning
confidence: 99%